FABRIKASI TINTA SPIDOL WHITEBOARD BERBAHAN DASAR PIGMEN ORGANIK DARI ENDAPAN MINUMAN KOPI - Amalia Puspita Rengganis; Sulhadi Sulhadi; Teguh Darsono; Dhamar Putra Fajar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
The ground of coffee drink does not have a high use value. An attempt has been made to utilize the coffee drink as an organic pigment for the whiteboard marker ink. Making organic pigment was done by reducing the particle size of coffee beverage using ball milling and screen mesh. The process of making the ink is by mixing the ingredients of ink such as Arabic gum, aquades, alcohol, and PEG on organic pigments. The process of making the ink is done by variation of arabic gum binder composition from 1 gram up to 3.5 grams. Based on the test result, the addition of arabic gum mass will increase the viscosity and level of ink adhesion. While in the transmittance test, the addition of arabic gum mass will decrease the intensity value of light transmitted by ink Keywords: Ink, Organic Pigment, Ground of Coffee.